Real world MRI experience with nonconditional and conditional cardiac rhythm devices after MagnaSafe. (1st November 2017) - Mason, Steve; Osborn, Jeffrey S.; Dhar, Ritesh; Tonkin, Allison; Ethington, Jon‐David; Le, Viet; Benuzillo, Jose; Lappe, Donald L.; Knowlton, Kirk U.; Bunch, T. Jared; Anderson, Jeffrey L.
Abstract: Introduction: The recent MagnaSafe Registry demonstrated safety of nonthoracic magnetic resonance imaging (MRI) with nonconditional cardiac implantable electronic devices (CIEDs). However, independent validation and extension to thoracic MRIs are needed. Methods and results: We prospectively examined 178 consecutive patients with CIEDs who underwent 212 MRI scans (62 with implantable cardioverter/defibrillators) for clinical reasons between February 2014 and August 2016. Scans were done in standard modes with a limit of 2 W/kg. Pacing modes were ODO or OVO for intrinsic rates > 40 and DOO or VOO for rates ≤ 40. Patients were cleared prescan by both radiology and cardiology, and pre‐ and postscan CIED interrogations were performed. Primary outcome events were death and generator or lead failure. Secondary events included battery voltage loss > 0.04 V, decrease in P wave voltage > 50% or R wave voltage > 25%, threshold increase of > 0.5 V, and impedance change > 50 Ω. Scan sites were 87 (41%) C‐spine/head/neck, 28 (13%) T‐spine/cardiac/shoulder (thoracic), 69 (33%) L‐spine/abdomen/pelvis, and 28 (13%) lower extremity. No primary or secondary outcome events occurred, and no periscan disruption of pacing was noted. Conclusion: In a real‐world MRI experience in patients with CIEDs representing a broad range of models, types, and scan sites (including thoracic scans), no adverse safety signals were noted. This experience validates and extends that of the large but inclusion‐restricted MagnaSafe Registry, profiles MRI scanning in CIED patients in general clinical practice, and argues against replacing nonconditional with conditional devices when MRI is performed in a carefully controlled environment.